ASSESSING HOSPITALITY STUDENTS’ SELF-KNOWLEDGE AND SOCIAL INFLUENCE TOWARD THEIR CAREER INTENTION - Azlina Samsudin; Amanina Mat Ghani; Malissasahila Abdul Manap; Mohd Hazrin Iman Noorkhizan; Wan Nor Bayah Wan Kamarudin (Journal of Islamic, Social, Economics and Development, 2022)
Students who understand the career insights accurately will understand theirstrengths and weaknesses and set clear career goals. This study includes final-year students ofHotel and Tourism Management who are required to undertake industrial attachment beforegraduation, as a requirement to complete their studies. Apparently, the students may haveperceptions of the current economic condition due to the COVID-19 crisis, which may affecttheir future career prospects in the industry. This study aims to assess hospitality students’career intentions based on self-knowledge and social influence. An online questionnaire wascollected among 489 (final-year) industrial training students of Hotel and TourismManagement, and Partial Least Squares-Structural Equation Modeling (PLS-SEM) softwarewas used to analyze the structuring of the data obtained using probability sampling. The resultsrevealed a significant and positive effect of Self-Knowledge (SK) and Social Influence (SI)towards Career intention (CI) of hospitality students. The findings indicate that therespondents’ perceptions of career intention induced by self-knowledge and social influenceprovide a noteworthy insight that is relatively imperative for educators and the governance ofthe institutions. Finally, the differences between the respondents are summarized, andrecommendations are drawn for educational institutions and further studies.